2021
DOI: 10.1080/07853890.2021.1890205
|View full text |Cite
|
Sign up to set email alerts
|

Stroke mimics: incidence, aetiology, clinical features and treatment

Abstract: Mimics account for almost half of hospital admissions for suspected stroke. Stroke mimics may present as a functional (conversion) disorder or may be part of the symptomatology of a neurological or medical disorder. While many underlying conditions can be recognized rapidly by careful assessment, a significant proportion of patients unfortunately still receive thrombolysis and admission to a high-intensity stroke unit with inherent risks and unnecessary costs. Accurate diagnosis is important as recurrent prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 85 publications
1
36
0
4
Order By: Relevance
“…On the other hand, population based data have shown that stroke is the underlying cause of epilepsy in older adults in more than 30% [6]. After having a post-stroke seizure recovery is rapid in most patients (see above) although rarely non-convulsive status epilepticus may present with prolonged aphasia or motor weakness [84].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, population based data have shown that stroke is the underlying cause of epilepsy in older adults in more than 30% [6]. After having a post-stroke seizure recovery is rapid in most patients (see above) although rarely non-convulsive status epilepticus may present with prolonged aphasia or motor weakness [84].…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms are mostly short-lived and show improvement within 24 h in most subjects. Recrudescence can develop within weeks to years after the previous stroke [84,100]. The recrudescence under metabolic, infection, fatigue or sedative medications is likely due to functional suppression of compensatory cerebral networks [84,100] (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Stroke mimic is a non-vascular disease characterized by acute neurological deficits comparable to those associated with stroke. According to several small studies, up to one-third of patients evaluated acutely by a stroke team and up to 15% of patients treated with intravenous tissue plasminogen activator (t-PA) have such stroke mimics; possible etiologies include seizures, tumors, migraine, infections, delirium, peripheral nerve injuries, multiple sclerosis, and conversion disorders [12][13][14].…”
Section: Stroke Mimicsmentioning
confidence: 99%
“…Stroke is a medical emergency and requires immediate evaluation, confirmation of diagnosis and treatment in order to prevent brain damage 16 . The acute ischaemic stroke chain of recovery involves recognition (of symptoms), reaction (emergency services alerted), response (medical assessment), reveal (brain imaging), and Rx (treatment initiation) 17 .…”
Section: Introductionmentioning
confidence: 99%